The Democratizing Influence of Intervention - Callaghan, Geoffrey D. (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2023)
Participation-based arguments in support of courts adopting a large and liberal attitude on intervention were persuasive at the outset of the Charter era. Due to the newness of the document at the time, a compelling case could be made that public participation in Charter challenges was a vital component of developing that document in a way that aligned with the core democratic commitments of the Canadian state. But the persuasiveness of such arguments has waned over time. If one accepts a common law approach to constitutional interpretation – where judicial activism is held in check by way of established precedent – arguments based on the participatory rights belonging to those potentially impacted by court decisions appear to be past their due date. This does not mean, however, that courts no longer have any democratic responsibilities concerning the practice of intervention. The positive contribution this article makes is to establish two alternative bases that can account for that responsibility — one inspired by the role intervention plays in encouraging public deliberation; and a second on the increased confidence the practice instills in judicial decision-making. In both cases, the ground of the responsibility is rather weak and can thus be easily defeated. Nevertheless, that courts have this responsibility at all offers a better explanation for why, even in times when an intervening party might not satisfy the strict criteria pertaining to the practice, there is reason to allow that intervention to proceed.